Efficacy and Safety of Ojeok-San Plus Saengmaek-San for Gastroesophageal Reflux-Induced Chronic Cough: A Pilot, Randomized, Double-Blind, Placebo-Controlled Trial - Lyu, Yee Ran; Kim, Kwan-Il; Yang, Changsop; Jung, So-Young; Kwon, O Jin; Jung, Hee-Jae; Lee, Jun-Hwan; Lee, Beom-Joon (Frontiers in Pharmacology, 2022)
Introduction: Gastroesophageal reflux-induced chronic cough (GERC) is one of the most common etiologies of chronic cough. Despite the growing prevalence and interest in GERC, no effective treatment is currently available. In our study, we used a combination of herbal medicines, Ojeok-san (OJS) plus Saengmaek-san (SMS), for the treatment of GERC. Methods: We conducted a pilot, randomized, placebo-controlled, parallel-arm, single-center clinical trial to assess the feasibility of our study protocol, as our study is the first herbal medicine trial for GERC. All enrolled participants were randomly assigned to either the intervention or placebo group in a 1:1 ratio and were administered trial drugs three times a day for 6 weeks, with an evaluation visit performed every 2 weeks for their efficacy and safety assessment until the follow-up visit (week 8). We evaluated the severity and frequency of cough, cough-specific quality of life, airway hypersensitivity, and reflux-related gastrointestinal symptoms, as well as pattern identification, to investigate the complex mechanisms of reflux cough syndrome. Results: A total of 30 participants were enrolled, and 25 completed the study at Kyung Hee University Korean Medicine Hospital from December 26, 2018, to May 31, 2021. OJS plus SMS significantly improved the cough diary score (CDS), cough visual analog scale, Korean version of the Leicester Cough Questionnaire, Hull Airway Reflux Questionnaire, and Gastrointestinal Symptom Rating Scale after the treatment compared to the baseline. Notably, OJS plus SMS showed significant efficacy in the daytime and total CDS compared with the placebo. Only one adverse event was observed during the trial, and no serious adverse events occurred. Additionally, we achieved successful results in feasibility outcomes by exceeding the ratio of 80%. Conclusion: We confirmed the feasibility of our trial design and demonstrated the potential of OJS plus SMS in relieving the severity of cough and GI symptoms in GERC patients with safe and successful feasibility results. We anticipate that our study results will be used as the basis for further large-scale, well-designed, confirmatory trials to evaluate the safety and efficacy of OJS plus SMS in GERC. Trial registration: This trial was registered at the Clinical Research Information Service (KCT0003115).